2015
DOI: 10.1016/j.jtcvs.2015.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Brahma-related gene 1 inhibits proliferation and migration of human aortic smooth muscle cells by directly up-regulating Ras-related associated with diabetes in the pathophysiologic processes of aortic dissection

Abstract: Our study illustrated that Brg1 inhibited the proliferation and migration capacity of HASMCs, via the mechanism of direct up-regulation of RRAD, thus playing an important role in the pathophysiologic processes of aortic dissection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 34 publications
1
18
0
Order By: Relevance
“…Müller BT, et al and Wang L, et al have reported that VSMCs from AD tissues seem to proliferate faster than normal aorta tissues and the genes that participate in proliferation showed an elevated level of expression [35, 36]. Furthermore, VSMC migration is also acknowledged as a crucial issue in AD pathogenesis [37, 38]. Our vitro functional experiments verified that downregulation of Talin-1 drastically enhanced the proliferation and migration capability of VSMCs which implied the occurrence of a positive pathological remodeling that was harmful to AD development.…”
Section: Discussionmentioning
confidence: 99%
“…Müller BT, et al and Wang L, et al have reported that VSMCs from AD tissues seem to proliferate faster than normal aorta tissues and the genes that participate in proliferation showed an elevated level of expression [35, 36]. Furthermore, VSMC migration is also acknowledged as a crucial issue in AD pathogenesis [37, 38]. Our vitro functional experiments verified that downregulation of Talin-1 drastically enhanced the proliferation and migration capability of VSMCs which implied the occurrence of a positive pathological remodeling that was harmful to AD development.…”
Section: Discussionmentioning
confidence: 99%
“…Further study confirms that Talin-1 regulates VSMC apoptosis and finally causes pathologic vascular remodeling to change vascular media structure and function and lead to TAD [22]. Many genes such as Sirtuin-1, PCSK9, and brahmarelated gene 1 had been reported to be associated with the pathophysiologic processes of TAD through influence proliferation and migration of VSMCs [23][24][25].…”
Section: Discussionmentioning
confidence: 54%
“…A 96-well plate was used for the assay, and the detailed procedures were performed as per our previous description, with modifications. 24 A total of 10 mL of CCK8 solution was added at 0, 24, 48, 72, and 96 hours after adenovirus transfection. Then, the cultures were incubated at 37 C with 5.0% carbon dioxide for 1.5 hours.…”
Section: Cell Proliferationmentioning
confidence: 99%
“…Then we evaluated the proliferation, migration, and apoptosis capabilities of VSMCs transfected with Ad-NANOG, which were considered as important functions of VSMCs in the pathogenesis of TAD. 8,24,29 We used CCK8 assay to evaluate the proliferation function of VSMCs. We found that VSMCs transfected with Ad-NANOG showed an enhanced proliferation function at 24, 48, 72, and 96 hours after transfection (Figure 4, A).…”
Section: Nanog Overexpression Promoted the Expression Of Opn And Vsmcmentioning
confidence: 99%
See 1 more Smart Citation